Evolution : the history of a scientific theory - Larson, Edward J. (Edward John) (New York : Modern Library, 2004)
Traces the history of evolutionary theory, from the eighteenth-century emergence of paleontology, through the breakthroughs of Darwin, to the backlash against evolutionism, to its resurrection through the science of genetics.
Includes bibliographical references (p. [315]-321) and index.
Keywords: Evolution (Biology) -- Philosophy -- History